Unearthing Unevenness of Potato Seed Networks in the High Andes: A Comparison of Distinct Cultivar Groups and Farmer Types Following Seasons With and Without Acute Stress - Arce, Alejandra; de Haan, Stef; Burra, Dharani D.; Ccanto, Raul (Frontiers in Sustainable Food Systems, 2018)
Farmer seed systems are considered pivotal to adaptation to climate change and the on-farm conservation of agrobiodiversity in centers of crop origin. To better understand their distinct role, we conducted a multipronged analysis of potato seed exchange networks in Peru’s central Andes distinguishing between cultivar groups and farmer types following cropping seasons with and without acute stress. Cultivar groups involved (i) bred varieties, (ii) commercial floury landraces, (iii) non-commercial floury landraces (single cultivars), (iv) non-commercial floury landraces (mixed cultivars), and (v) bitter landraces. Farmer types involved (i) general farmers, (ii) seed specialists, and (iii) custodian farmers. Documentation of seed acquisition and provision without differentiating between farmers and cultivar groups may not accurately reflect the fine-grained dynamics underlying seed networks. To test this, a semi-structured survey of 336 households was conducted in 2014-2015 to study seed procurement in two research sites. Results confirm that seed networks are uneven and distinct for cultivar groups and farmer types. Commercial floury landraces and bred varieties were dominant when it came to frequency of transactions, volumes and overall availability. Bitter landraces represent an extreme opposite case, being procured infrequently. Non-commercial floury landraces represent an intermediate case as they are regularly procured in comparatively small volumes. The influence of general farmers and traders within seed networks is essential for overall seed access. The role of specialists and custodians is less omnipresent; yet, both fulfill a unique role. Specialists as providers of large volumes of certified seed of commercial floury landraces and bred varieties. Custodians as a source of diverse non-commercial floury landraces. Seed networks did re-organize following seasons with acute seed stress. A notable shift involved a contraction of seed networks within sub-regional clusters. Following stress, the directionality of seed provision versus acquisition inverted. While average seed volumes acquired per transaction nearly halved, farmers´ net seed acquisitions surpassed provisions in response to stress. We suggest that the self-regulatory capacity of farmer seed networks represents a strong safety net through which smallholders can respond to crop failure and seed stress. Seed system interventions aimed at genetic resources conservation or relief should build on these seed networks.